2013
DOI: 10.5047/eps.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of subsurface lineaments in the southwestern part of the Thrace Basin from gravity data

Abstract: Linear anomalies, as an indicator of the structural features of some geological bodies, are very important for the interpretation of gravity and magnetic data. In this study, an image processing technique known as the Hough transform (HT) algorithm is described for determining invisible boundaries and extensions in gravity anomaly maps. The Hough function implements the Hough transform used to extract straight lines or circles within twodimensional potential field images. It is defined as image and Hough space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…From stratigraphic cross section [20], it is inferred that the density contrasts for left and right layers of the fault can be set to different values. From previous studies [5][6][7][8][9], it is inferred that the thickness of the area is around 4-5km. It is concluded that case II agrees with the geologic information provided in the area and is considered as an appropriate solution for this profile.…”
Section: Results and Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From stratigraphic cross section [20], it is inferred that the density contrasts for left and right layers of the fault can be set to different values. From previous studies [5][6][7][8][9], it is inferred that the thickness of the area is around 4-5km. It is concluded that case II agrees with the geologic information provided in the area and is considered as an appropriate solution for this profile.…”
Section: Results and Dicussionmentioning
confidence: 99%
“…[7] firstly mapped faults in the southwestern of the Thrace basin and reported that the faults lying in this area include several normal faults and mostly strike-slip faults according to their field observations. [8] have determined lineaments in the southwestern of the Thrace basin using Hough transform from gravity data.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lineament mapping is a crucial element in many geological studies, especially in mineral and hydrocarbon exploration [22,29] as well as in hydrogeology [20]. Additionally, lineaments can be employed for structural analysis to understand and reconstruct the geological history of a region [28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Gravity and Magnetic geophysical methods are used to determine the spatial variations of the subsurface rock density and magnetic susceptibility which cause small variations in the earth's gravitational and magnetic fields respectively. Gravity and magnetic surveys are often the initial reconnaissance surveys prior to other types of survey such as seismic shooting (Ghaib, 2001;Aydogan et al, 2013). Magnetic readings were not interpreted quantitatively, because no adequate information about the magnetic properties of surface and subsurface rocks is present.…”
Section: Introductionmentioning
confidence: 99%